In Situ Modulation of Al Traces and Interlayer Spacing in Ti3C2Tx ‐A2 MXene: Supercapacitor with Ultrahigh Capacitance and Energy Density. Issue 27 (17th August 2022) - Kumari, Shilpa; Aagar, Srinivasan; Sharma, Amit Kumar; Upreti, Deepak; Aashi,; Agrawal, Garima; Bagchi, Vivek
Abstract: Although Ti3 C2 Tx MXene is known as a unique 2D layered material with high metal conductivity and redox‐active surface, and is widely employed as a supercapacitor electrode, however, its capacitance maximization is severely limited, due to restacking of the MXene flakes. To get around this problem, an innovative etching technique is employed to circumvent the issue of restacking without using a separate delamination procedure. This is done by keeping optimum Al traces inside the Ti3 C2 Tx layers by tuning the ratio of LiF and Ti3 AlC2 precursors at room temperature. Instead of obtaining solitary Ti3 C2 Tx flakes, the Al‐trace in Ti3 C2 Tx ‐A2 holds a stable layered structure, facilitates easier electrolyte mobility, and prevent the possibility of restacking. As synthesized material, Ti3 C2 Tx ‐A2 exhibits excellent gravimetric capacitance of 513 F g –1 at 2 A g –1 with 80% capacitance retention up to 10 000 cycles at a current density of 12 A g –1 . The all‐solid‐state symmetric supercapacitor (ASSS) can deliver a significant gravimetric energy density of 14.5 W h Kg –1 and areal energy density of 49.2 mW h cm –2 . The established technique enables Ti3 C2 Tx MXenes to improve their capacitive performance and explore their application in energy storage devices. Abstract : To circumvent the restacking of the Ti3 C2 Tx MXene flakes, herein an inventive etching method is used without further delamination. This is accomplished by adjusting the ratio of LiF and Ti3 AlC2 during etching at room temperature to maintain optimum Al traces inside the Ti3 C2 Tx layers to get a stable layered structure having high capacitance and energy density of 14.5 Wh Kg ‐1 .